The malevolent side of masstige consumers’ behavior: The role of dark triad and technology propensity - Iaia, Lea; Leonelli, Simona; Masciarelli, Francesca; Christofi, Michael; Cooper, Sir Cary L. (My University, 2022)
Masstige marketing represents the democratization of luxury to middle-class consumers. The purchase of luxury brands aims to satisfy utilitarian and hedonic customers’ motives, based on their personality traits, even the dark ones (such as narcissism, Machiavellianism, and psychopathy). The continuous evolution of technologies pushes consumers to face their technological adoption propensity. Smartphones can be considered as objects able to extend the self of consumers and their status. The interest of our research is to investigate the masstige perception of smartphone brands, through the lens of the antecedents of consumers' behavior and the dark side of their personalities. The relationship is explored considering the technological propensity of consumers. We analyzed three market leader brands in the smartphone industry – Apple (iPhone), Samsung, and Huawei. The research contributes to the academic literature on the impact of the dark side of personalities on masstige marketing and technology adoption propensity.
Keywords: Dark triad; Masstige marketing; Personality traits; Smartphone brands; Technology adoption propensity